The prevalence of cognitive impairment in laryngology treatment–seeking patients. (25th October 2019) - Leclerc, Andrée‐Anne; Gillespie, Amanda I.; Tadic, Stasa D.; Smith, Libby J.; Rosen, Clark A.
Abstract : Objectives/Hypothesis: The incidence of cognitive impairment (CI) in the elderly general population is 10% to 20%. The incidence of CI in the elderly laryngology treatment–seeking population is unknown, and CI may impact decision making for elective medical/surgical treatment and negatively impact the outcome of voice/swallowing therapy. We sought to determine the prevalence of CI in elderly patients who are seeking laryngology care and to evaluate the feasibility of administering a cognitive screening instrument. Study Design: Prospective, Cross‐sectional. Methods: One hundred fifty patients (≥65 years old) without a previous diagnosis of CI, seeking laryngology evaluation, were administered the Montreal Cognitive Assessment (MoCA) test by a trained physician. Other members of the clinical team were blinded to the MoCA results. Results: Twenty‐five percent of participants obtained a score diagnostic for at least mild CI. The results showed a correlation between the MoCA scores and 1) the time needed to complete the test, 2) participant age, and 3) participant education level. No differences were observed between gender, alcohol consumption, or use of medications that can affect cognition and MoCA score. Conclusion: One in four elderly laryngology treatment‐seeking patients were found to have undiagnosed CI. This finding warrants consideration for CI screening for these patients being evaluated for voice therapy and elective surgery. Treatment decision making in this population may benefit from additional family involvement. Level of Evidence: 2c Laryngoscope, 130: 2003–2007, 2020